Indentation size effect–crack propagation model and finite element simulation verification for microhardness test of ceramic materials. Issue 4 (15th February 2021) - Luo, Junting; Wang, Haotian; Xi, Chenyang; Zhai, He; Gu, Yongfei; Zhang, Chunxiang
Abstract: In this study, an indentation size effect–crack propagation model for hard and brittle materials in microhardness testing was proposed on the basis of the relationship between the size effects in microhardness testing and the generation and propagation of cracks in an indentation area. Results showed that crack length and crack opening angle were the main factors that influenced the size effect. The longer the crack length, the larger the crack opening angle, and the more obvious the size effect. The generation and propagation of cracks in the indentation region of ultrafine-grained Si2 N2 O–Si3 N4 ceramics during microhardness testing were simulated on ABAQUS finite element software. The distributions of displacement field, strain field, and stress field in the indentation area with the presence of cracks was analyzed, the influence of crack propagation on the elastic recovery of the indentation area was discussed, and the correctness of the size effect–crack propagation model was verified.